Maternal clinical predictors of preterm birth in twin pregnancies: A systematic review involving 2, 930, 958 twin pregnancies. (November 2018) - Marleen, Shemoon; Hettiarachchi, Janitha; Dandeniya, Ranmalie; Macgreggor, Rebecca; Aquilina, Joseph; Khalil, Asma; Vogel, Joshua; Betrán, Ana P.; Thangaratinam, Shakila
Abstract: In twin pregnancies, which are at high risk of preterm birth, it is not known if maternal clinical characteristics pose additional risks. We undertook a systematic review to assess the risk of both spontaneous and iatrogenic early (<34 weeks) or late preterm birth (<37 weeks) in twin pregnancies based on maternal clinical predictors. We searched the electronic databases from January 1990 to November 2017 without language restrictions. We included studies on women with monochorionic or dichorionic twin pregnancies that evaluated clinical predictors and preterm births. We reported our findings as odds ratio (OR) with 95% confidence intervals (CI) and pooled the estimates using random-effects meta-analysis for various predictor thresholds. From 12, 473 citations, we included 59 studies (2, 930, 958 pregnancies). The risks of early preterm birth in twin pregnancies were significantly increased in women with a previous history of preterm birth (OR 2.67, 95% CI 2.16–3.29, I 2 = 0%), teenagers (OR 1.81, 95% CI 1.68–1.95, I 2 = 0%), BMI > 35 (OR 1.63, 95% CI 1.30–2.05, I 2 = 52%), nulliparous (OR 1.51, 95% CI 1.38–1.65, I 2 = 73%), non-white vs. white (OR 1.31, 95% CI 1.20–1.43, I 2 = 0%), black vs. non-black (OR 1.38, 95% CI 1.07–1.77, I 2 = 98%), diabetes (OR 1.73, 95% CI 1.29–2.33, I 2 = 0%) and smokers (OR 1.30, 95% CI 1.23–1.37, I 2 = 0%). The odds of late preterm birth were also increased in women with history of preterm birth (OR 3.08, 95% CI 2.10–4.51, I 2 = 73%), teenagers (OR 1.36, 95% CI 1.18–1.57, I 2 = 57%), BMI > 35 (OR 1.18, 95% CI 1.02–1.35, I 2 = 46%), nulliparous (OR 1.41, 95% CI 1.23–1.62, I 2 = 68%), diabetes (OR 1.44, 95% CI 1.05–1.98, I 2 = 55%) and hypertension (OR 1.49, CI 1.20–1.86, I 2 = 52%). The additional risks posed by maternal clinical characteristics for early and late preterm birth should be taken into account while counseling and managing women with twin pregnancies.